Role of pattern-recognition receptors in cardiovascular health and disease. (23rd November 2007) - Mitchell, J.A.; Ryffel, B.; Quesniaux, V.F.J.; Cartwright, N.; Paul-Clark, M.
Abstract : A role for PRRs (pattern-recognition receptors) in immune cell function is now well established. In macrophages and other immune cells, activation of TLRs (Toll-like receptors) and cytosolic NLRs [NOD (nucleotide oligomerization domain) proteins containing a leucine-rich repeat] results in the induction of genes and release of imunoregulator hormones including cytokines and NO (nitric oxide). In addition to immune cells, structural cells of the cardiovascular system including endothelial cells, vascular smooth muscle and cardiac myocytes express functional PRRs and sense PAMPs (pathogen-associated molecular patterns). Furthermore, bacteria and PAMPs activate the coagulation system and platelets. TLRs are now implicated in a range of cardiovascular diseases and syndromes including atherosclerosis and sepsis. Our group is working on the hypotheses that differences exist in how tissues of the cardiovascular system, including vessels, endothelium, heart and blood, sense pathogens compared with immune cells (principally macrophages) and that identifying such differences will reveal new therapeutic targets for the treatment of cardiovascular disease. We have identified examples of similarities and differences in how cardiovascular tissues and macrophages sense PAMPs. These findings will be discussed together with our interpretation of how this information may lead to new treatments.